A REGIONAL REFINEMENT FOR FINITE ELEMENT MESH DESIGN USING COLLAPSIBLE ELEMENT - Priyo Suprobo; Tavio Tavio (Civil Engineering Dimension, 2000)
A practical algorithm for automated mesh design in finite element analysis is developed. A regional mixed mesh improvement procedure is introduced. The error control%2C algorithm implementation%2C code development%2C and the solution accuracy are discussed. Numerical example includes automated mesh designs for plane elastic media with singularities. The efficiency of the procedure is demonstrated. Abstract in Bahasa Indonesia : regional+refinement%2C+mesh+generation%2C+isoparametric+element%2C+collapsible+element